The kinetics of oxygen electroreduction: a long way from iron rust to lithium-air batteries - Calvo, Ernesto Julio (2014)
In this communication, we review the details of the oxygen electroreduction reaction on rust layers, passive iron and well defined iron oxides as cathodes for the reaction. In particular, we highlight the important electrocatalytic role of Fe(II) sites at the surface of the oxides in contact with the aqueous electrolyte. When the same reaction takes place at bifunctional cathodes with separated metal anodes which gives rise to metal–air batteries on which much attention has been paid recently in connection with electric vehicles.